2018
DOI: 10.2147/cmar.s175501
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of TIGAR and LC3B protein expression in nasopharyngeal carcinoma

Abstract: PurposeAutophagy, the process responsible for degrading cytoplasmic organelles to sustain cellular metabolism, has been associated with cancer initiation and progression. As TP53-induced glycolysis and apoptosis regulator (TIGAR) is among the important genes that can regulate autophagy, we aimed to investigate the correlation between the expression levels of TIGAR and the autophagy-related protein microtubule-associated protein 1 light chain 3 (LC3B), as well as their association with clinical outcomes, in nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…TIGAR is highly expressed in many cancer types, driving proliferation, migration, invasion, crosstalk with NFkB and tumor burden 20‐25 . TIGAR drives breast cancer tumor growth with glycolysis in fibroblasts and utilization of lactate to fuel OXPHOS and ATP production in carcinoma cells 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIGAR is highly expressed in many cancer types, driving proliferation, migration, invasion, crosstalk with NFkB and tumor burden 20‐25 . TIGAR drives breast cancer tumor growth with glycolysis in fibroblasts and utilization of lactate to fuel OXPHOS and ATP production in carcinoma cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…TIGAR is highly expressed in many cancer types, driving proliferation, migration, invasion, crosstalk with NFkB and tumor burden. [20][21][22][23][24][25] TIGAR drives breast cancer tumor growth with glycolysis in fibroblasts and utilization of lactate to fuel OXPHOS and ATP production in carcinoma cells. 8 Together these studies demonstrate TIGAR expression drives cancer progression and aggressiveness, but the mechanisms remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TIGAR has been reported to be involved in different stages of cancer progression, including development and metastasis 16 , 17 , 18 . High levels of TIGAR were observed in multiple types of cancers and correlated strongly with poor survival of patients in chronic lymphocytic leukemia, ovarian cancer, lung cancer and nasopharyngeal carcinoma 9 , 17 , 19 , 20 , 21 . Moreover, several studies showed that TIGAR was associated with cancer therapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been achieved in the treatment of NPC with the development of intensity-modulated radiotherapy (IMRT), but the local recurrence and distant metastasis rates after treatment are still more than 30% 2 . It is known that the survival and prognosis of patients with NPC are affected by several factors, such as the TNM stage, TIGAR, TC3B, and other biological factors 3 , 4 . The identification of more effective biomarkers not only facilitates prognosis prediction, but also provides promising targets for treatment purposes, which would be extremely useful for NPC patients.…”
Section: Introductionmentioning
confidence: 99%